Development of a control algorithm for active control of rolling motion of a ship using a gyrostabilizer - Song, Ki-Seok; Kim, Soo-Min; Kwak, Moon K.; Zhu, Weidong (Ocean engineering, 2023)
In this study, a new control algorithm for an active gyrostabilizer was developed and applied to a ship model. The active gyrostabilizer consists of a gyro sensor that measures the angular rate of the rolling motion of a ship, a controller that realizes the active control algorithm, and an actuator that is connected to the precession axis. The new control algorithm receives the angular rate of the ship, then outputs the desired precession angle. A suitable actuator for this kind of mission could be a servomotor. Based on the concept of tuned mass damper, a new control algorithm for an active gyrostabilizer was developed. It was theoretically found that instead of increasing stiffness, the damping of the rolling motion of the ship could be increased by tuning the filter frequency of the control algorithm to the rolling frequency. The results of both numerical and experimental investigations showed that the proposed control algorithm is valid and can be used to effectively suppress rolling motion with a relatively low speed or light spinning wheel compared to passive gyrostabilizers. •A new control algorithm based on the concept of tuned mass damper for an active gyrostabilizer is developed.•The proposed control algorithm can enhance roll damping and quickly suppress the rolling of a ship.•The effectiveness of the control algorithm is demonstrated theoretically and experimentally.•The proposed active gyrostabilizer can be built with relative ease.